1993
DOI: 10.3758/bf03206785
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms in the haptic horizontal-vertical illusion: Evidence from sighted and blind subjects

Abstract: The haptic horizontal-vertical illusion was studied in two experiments. In Experiment 1, the illusion was relatively weak in sighted subjects and depended on stimulus size and the nature of the figure, that is, whether the pattern was an inverted-T or L shape. Experiment 2 compared early blind and late blind subjects. The illusion was present for an inverted-T figure but absent for an L figure in late blind subjects. However, the early blind subjects treated both the Land T figures as similar and showed the il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 25 publications
1
31
1
Order By: Relevance
“…If the same factors influence the strength of the illusion in both domains, this indicates similar perceptual processes underlying the illusion. It could be shown that bisection effects and vertical overestimation are also present when participants judge the length of the elements by touch (Heller, Calcaterra, Burson, & Green, 1997;Heller & Joyner, 1993). Heller and colleagues found that the HVI occurs with touch but that the magnitude of the effect depends on visual experience and stimulus size.…”
Section: Evidence In the Haptic Domainmentioning
confidence: 99%
See 2 more Smart Citations
“…If the same factors influence the strength of the illusion in both domains, this indicates similar perceptual processes underlying the illusion. It could be shown that bisection effects and vertical overestimation are also present when participants judge the length of the elements by touch (Heller, Calcaterra, Burson, & Green, 1997;Heller & Joyner, 1993). Heller and colleagues found that the HVI occurs with touch but that the magnitude of the effect depends on visual experience and stimulus size.…”
Section: Evidence In the Haptic Domainmentioning
confidence: 99%
“…When T and L figures were presented in a frontoparallel plane, where all exploratory movements are tangential, the bisection effect in the T figure remained, whereas the vertical segments in the L figure were no longer overestimated (Day & Avery, 1970;Deregowski & Ellis, 1972). These works point out the importance of scanning (exploration) methods, spatial reference cues or reference frames, anchors, and so on (for a review, see Gentaz & Hatwell, 2004;Heller & Joyner, 1993;Millar & Al-Attar, 2000). The strength of the illusion was generally found to be similar for sighted and blind participants, ruling out that visual imagery or visual representations are responsible for the haptic illusion.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, curvature perception depends on whether the curvature is convex or concave (van der Horst & , the direction of movement over the surface (Davidson, 1972;Hunter, 1954), the position of the stimulus on the hand (Pont, Kappers, & Koenderink, 1997, 1998, and on shape features other than the judged curvature (Vogels, Kappers, & Koenderink, 1999). Haptic perception of linear extent is affected by the path length, curvature (Sanders & Kappers, 2008), rate of exploration between endpoints (Armstrong & Marks, 1999;Lederman, Klatzky, & Barber, 1985), and other linear elements in the field (Heller & Joyner, 1993).…”
Section: Manual Exploration For Haptic Perceptionmentioning
confidence: 99%
“…Day comments that they have been described for a long time [18,66]. Suzuki and Arashida looked at the relative effectiveness of various figures, Müller-Lyer, Oppel-Kundt, Bourdon, Ponzo, Poggendorf, vertical-horizontal, Zöllner, Delboeuf [74], while Heller and Joyner considered the horizontal-vertical effect comparing the behavior blind and sighted people [40]. These effects motivated a significant number of recent studies [77,57,33].…”
Section: Geometrical Illusions Bourdon Müller-lyer and Othersmentioning
confidence: 99%